Use of augmented-reality in teaching energy efficiency: prototype development and testing - Rashed-Ali, Hazem; Quarles, John; Fies, Carmen; Sanciuc, Levi (ARCC Conference Repository, 2014)
Passive solar and energy efficiency concepts are usually taught through lectures, textbooks, or hands-on experimentation, but the relationship between these concepts istypically not effectively visualized. To address this, this paper reports on the design, development and preliminary testing of a prototype Augmented Reality (AR) application for residential energy use education. This tablet-based AR application simulates the impact of different residential building design characteristics on both indoor temperature (for passiveheating/cooling) and annual energy use and cost (for mechanical HVAC). The application was developed by an interdisciplinary team of researchers/educators from three related fields: architecture, interdisciplinary education, and computer science. AR consists of additional information that is visible through a technology interface, shown on top of the images of the real world under study within a digital 3D space. The interdisciplinary model presented in this paper integrates three distinct lenses: 1) passive design and energy efficiency education 2) ARas an interactive modality and 3) a computationally complex building performance simulation model. In particular, the paper reports on the results of an experiment in which junior-level university students in a school of architecture used the prototype. Results from the pre and post knowledge surveys conducted within the experiment show consistent and high improvement in the students' confidence in their knowledge of the topics following the use of the prototype. Student feedback was also generally positive but some issues were identified which may indicate that this prototype would be more effective at the freshmen level. Plans for future development phases for this project include focusing on this new population. The project described in this paper also illustrates the considerable potential that interdisciplinary collaboration offers for architectural research through enabling architectural researchers to tackle more complex issues and developing a better understanding of the research approaches and expectations in other disciplines.